Confusion Assessment Method for the intensive care unit (CAM‐ICU) for the diagnosis of delirium in adults in critical care settings - Miranda, Fabian (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Diagnostic test accuracy). The objectives are as follows: To determine the diagnostic accuracy of the Confusion Assessment Method for the Intensive Care Unit (CAM‐ICU) for the diagnosis of delirium in adult patients in critical care settings.